Waterproof, air-permeable and moisture-permeable fabric and preparation method thereof
By using thermoplastic polyurethane and chitosan to prepare electrospinned nanofiber membranes and adding nanocharcoal balls/hydrotalcium sheet-like materials, the problem of reduced moisture permeability of existing waterproof and moisture permeable films is solved, and efficient moisture permeability is achieved and Waterproof, suitable for advanced functional fabrics.
Patent Information
- Application Number
- CN202411380671.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The moisture permeability of the existing waterproof and moisture permeable film gradually decreases after use for a period of time, which cannot meet the improvement of people's functional requirements.
The electrospinned nanofiber membrane is prepared using thermoplastic polyurethane and chitosan as raw materials, and compounded with the fabric to form a composite fabric with waterproof, breathable and moisture-permeable properties. By adding nanocharcoal balls/hydrotalc to the chitosan electrospinning membrane Sheet-like material, improving hydrophobicity and porous structure.
It achieves the improvement of moisture permeability while maintaining waterproofness and breathability, and can maintain good functionality after washing. It is suitable for high-quality functional fabrics such as windbreakers.
Smart Images

Figure BDA0005069821050000111 
Figure BDA0005069821050000121
Abstract
Description
Technical Field
[0001] The invention relates to the field of functional fabrics, and in particular to a waterproof, breathable and moisture-permeable fabric and a preparation method thereof. Background Art
[0002] The waterproof and breathable membrane is the core material of waterproof and breathable functional clothing. While resisting external wind, frost, rain and snow, it can transfer the evaporated sweat from the body surface to the outside, so that the microenvironment on the human body surface remains balanced to ensure the comfort of the human body. Due to its special functions, the waterproof and breathable membrane can not only ensure that the human body remains comfortable in harsh climate environments, but also meet the needs of indoor and outdoor sports. Under certain conditions, it can also play an isolation role. Waterproof and breathable membranes are widely used in various industries. For example, they are often used in outdoor clothing such as assault jackets and ski suits and outdoor equipment such as tents in outdoor sports. In medical treatment, they are mainly used for surgical gowns, bed sheets, wound dressings, etc. In the military, they are mainly used for combat uniforms, cold-proof clothing, etc. In firefighting, they are mainly used for special protection, etc. At present, waterproof and breathable membranes are mainly used in outdoor clothing, and due to their special properties, the market demand continues to increase. In recent years, with the advancement of science and technology and the improvement of people's living standards, waterproof and breathable fabrics have developed rapidly and have been applied to many fields. At present, the waterproof and breathable products with excellent performance on the market are mainly from the United States. Series of products and waterproof breathable membranes and fabrics produced by Sympatex of Germany. Gore-Tex is light, thin and durable. It not only has good waterproofness and breathability but also has good windproofness. Its appearance has changed the shortcomings of the general waterproof membrane on the market. With the development of several generations of Gore-Tex, its products have been continuously improved in breathability while maintaining waterproofness and durability, and the comfort can better meet the requirements of the market and consumers. At present, In addition to being widely used in various outdoor sports, the series of products are also used in military, safety and firefighting equipment. Sympatex is a hydrophilic non-porous membrane made of copolyether ester. By compounding the Sympatex film with different fabrics, a composite structure with different uses is obtained. Sympatex film has a high market share in Europe. This film is composed of 100% polyester and decomposes into nitrogen, hydrogen and oxygen under natural conditions. Therefore, it is environmentally friendly and can be recycled. In addition, since it uses the macromolecular chains in the hydrophilic non-porous membrane for moisture conduction, its moisture permeability will not be affected by scratching or washing after a period of use. However, as people's requirements for functionality increase, its moisture permeability gradually cannot meet people's requirements. Summary of the invention
[0003] Technical problem to be solved: The purpose of the present invention is to provide a waterproof, breathable and moisture permeable fabric, which is prepared by electrospinning nanofiber membrane using thermoplastic polyurethane and chitosan as raw materials, and then compounded with fabric to obtain a fabric that is both waterproof, moisture permeable and breathable.
[0004] Technical solution: A waterproof, breathable and moisture-permeable fabric, the fabric comprising a TPU layer, a fabric layer, and a moisture-wicking and waterproof layer, the TPU layer is a TPU electrospun membrane, the moisture-wicking and waterproof layer is a chitosan electrospun membrane, and the chitosan electrospun membrane contains nano-carbon balls / hydrotalcite flake materials. Preferably, the method for preparing the nano carbon ball / hydrotalcite flake material comprises the following steps: S11. Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were added to deionized water in a molar ratio of 3:1, and stirred to dissolve to obtain a mixed salt solution; S12. Sodium hydroxide and sodium carbonate were added to deionized water in a molar ratio of 1:1, stirred and dissolved to obtain a mixed alkaline solution; S13. The mixed salt solution and the mixed alkali solution were added dropwise to the container at the same rate, stirring the reaction, always maintaining the pH of the mixed solution at 10-11, and the reaction was heated after the addition was completed to obtain magnesium aluminum hydrotalcite; S14. The magnesium aluminum hydrotalcite was added to formamide, stirred for 20-60h, and the supernatant was collected by centrifugation, washed and dried to obtain the exfoliated magnesium aluminum hydrotalcite; S15. The exfoliated magnesium aluminum hydrotalcite is added to a fructose aqueous solution, and then added to a hydrothermal reactor for heating to react to obtain a nano-carbon ball / hydrotalcite sheet material; S16. Add the nano carbon sphere / hydrotalcite flake material to anhydrous ethanol, stir and disperse evenly, then add stearic acid, mix evenly to obtain a suspension, keep the solution pH at 5.5, stir to react, and dry to obtain a modified nano carbon sphere / hydrotalcite flake material. Preferably, the temperature of the heating reaction in step S13 is 70-90°C and the time is 4-10h. Preferably, in step S15, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution is 2-8wt%, the concentration of the fructose aqueous solution is 0.2-0.6mol / L, the hydrothermal reaction temperature is 170-185°C, and the hydrothermal reaction time is 8-20h. Preferably, in step S16, the mass ratio of the nano carbon balls / hydrotalcite flake material to stearic acid is 5-8:1. The preparation method of the above-mentioned waterproof, breathable and moisture-permeable fabric comprises the following steps: S1. dissolving thermoplastic polyurethane in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 8-10%, and electrospinning the TPU to obtain a TPU electrospinning membrane; S2. The fabric is immersed in a 0.1-0.3wt% chitosan solution, stirred for reaction and then dried, the TPU electrospun membrane is bonded to one side of the fabric layer by hot pressing, and then a layer of chitosan wet gel is coated on the side of the TPU electrospun membrane that is not bonded to obtain a fabric layer; S3. Add the nano carbon ball / hydrotalcite flake material to the chitosan solution, stir and mix evenly, use the side of the fabric layer containing the chitosan wet gel as the receiving surface, and prepare a moisture-repelling and waterproof layer on the outside of the fabric layer through electrospinning, and finally freeze-dry to obtain a waterproof, breathable and moisture-permeable fabric. Preferably, the porosity of the electrospinning membrane in step S1 is 60-70%. Preferably, the thickness of the chitosan hydrogel in step S2 is 0.1-0.2 mm. Preferably, in step S3, the concentration of the nano carbon balls / hydrotalcite flake material in the chitosan solution is 5-8wt%, the concentration of the chitosan solution is 0.8-1.2wt%, and the porosity of the moisture-draining and waterproof layer is 80-90%. Preferably, the freeze-drying temperature in step S3 is -60 to -40°C and the time is 10 to 20 hours. Beneficial effects: The waterproof, breathable and moisture-permeable fabric of the present invention has the following advantages: 1. The present invention adopts a hydrophobic TPU layer, a fabric layer and a moisture-wicking and waterproof layer to obtain a composite fabric with directional moisture conduction; before the fabric is composited with TPU, the fabric is first soaked in a relatively low concentration chitosan solution so that the pores of the fabric are infiltrated with chitosan, and the chitosan infiltrated in the pores acts as a capillary, and after the fabric is soaked in low-concentration chitosan, a layer of wet chitosan gel is coated on the surface of the fabric. The wet chitosan gel can play two roles. First, the chitosan gel surface is directly electrospun, and the composite of the electrospinning membrane and the fabric does not require the addition of an adhesive. The chitosan electrospinning membrane can adhere well to the chitosan wet gel. Secondly, after the wet gel is dried, it can quickly evaporate the water adsorbed in the pores through the porous structure, thereby improving the air permeability and moisture permeability effect; 2. The present invention prepares fructose on the surface of micro-nano hydrotalcite by hydrothermal reaction in a fructose solution, wherein fructose contains nano-carbon microspheres on the surface of the micro-nano hydrotalcite, and finally undergoes hydrophobic modification. The prepared nano-carbon microsphere / hydrotalcite flaky material is then added to the chitosan spinning solution. The prepared fiber membrane has a multi-level rough structure and low surface energy, achieving super-hydrophobic properties. At the same time, the composite nanofiber membrane has a hydrophobic porous structure, which can prevent liquid water from penetrating while transferring water vapor. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 A method for preparing a waterproof, breathable and moisture-permeable fabric, the method comprising the following steps: S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 10%, and the TPU was electrospun to obtain a TPU electrospinning membrane with a porosity of 62.8%; S2. The fabric is immersed in a 0.1wt% chitosan solution, stirred for reaction and then dried, the TPU electrospun membrane is bonded to one side of the fabric layer by hot pressing, and then a layer of chitosan wet gel with a thickness of 0.1mm is coated on the side where the TPU electrospun membrane is not bonded to obtain a fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%; S3. Adding the nano carbon ball / hydrotalcite flake material to a chitosan solution with a concentration of 0.8wt%, wherein the concentration of the nano carbon ball / hydrotalcite flake material in the chitosan solution is 8wt%, stirring and mixing evenly, using the side of the fabric layer containing the wet chitosan gel as the receiving surface, preparing a moisture-wicking and waterproof layer with a porosity of 81.5% on the outside of the fabric layer by electrospinning, and finally freeze-drying at a freeze-drying temperature of -60°C for 20h to obtain a waterproof, breathable and moisture-permeable fabric; The method for preparing the nano carbon ball / hydrotalcite flake material comprises the following steps: S11. Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were added to deionized water in a molar ratio of 3:1, and stirred to dissolve to obtain a mixed salt solution; S12. Sodium hydroxide and sodium carbonate were added to deionized water in a molar ratio of 1:1, stirred and dissolved to obtain a mixed alkaline solution; S13. The mixed salt solution and the mixed alkali solution were added dropwise to the container at the same speed, stirred and reacted, and the pH of the mixed solution was always kept at 10. After the addition was completed, the reaction was heated at a temperature of 70 ° C for 10h to obtain magnesium aluminum hydrotalcite; S14. The magnesium aluminum hydrotalcite was added to formamide, stirred for 60 hours, and the supernatant was collected by centrifugation, washed and dried to obtain the exfoliated magnesium aluminum hydrotalcite; S15. The stripped magnesium aluminum hydrotalcite was added to a 0.2 mol / L fructose aqueous solution, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution was 2 wt%, and then added to a hydrothermal reactor for heating reaction, the hydrothermal reaction temperature was 170 ° C, the hydrothermal reaction time was 20 h, and a nano-carbon ball / hydrotalcite sheet material was obtained; S16. Add the nano carbon ball / hydrotalcite flake material to anhydrous ethanol, stir and disperse evenly, then add stearic acid, the mass ratio of the nano carbon ball / hydrotalcite flake material and stearic acid is 5:1, mix evenly to obtain a suspension, maintain the solution pH at 5.5, stir to react, and dry to obtain the modified nano carbon ball / hydrotalcite flake material. Example 2 A method for preparing a waterproof, breathable and moisture-permeable fabric, the method comprising the following steps: S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 8%, and the TPU was electrospun to obtain a TPU electrospinning membrane with a porosity of 65.3%; S2. The fabric is immersed in a 0.3wt% chitosan solution, stirred for reaction and then dried, the TPU electrospun membrane is bonded to one side of the fabric layer by hot pressing, and then a layer of chitosan wet gel with a thickness of 0.2mm is coated on the side where the TPU electrospun membrane is not bonded to obtain a fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%; S3. Add the nano carbon ball / hydrotalcite flake material to a chitosan solution with a concentration of 1.2wt%, wherein the concentration of the nano carbon ball / hydrotalcite flake material in the chitosan solution is 5wt%, and stir to mix evenly, and use the side of the fabric layer containing the wet chitosan gel as the receiving surface, and prepare a moisture-repellent waterproof layer with a porosity of 82.6% on the outside of the fabric layer by electrospinning, and finally freeze-dry at a freeze-drying temperature of -40°C for 1h to obtain a waterproof, breathable and moisture-permeable fabric; The method for preparing the nano carbon ball / hydrotalcite flake material comprises the following steps: S11. Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were added to deionized water in a molar ratio of 3:1, and stirred to dissolve to obtain a mixed salt solution; S12. Sodium hydroxide and sodium carbonate were added to deionized water in a molar ratio of 1:1, stirred and dissolved to obtain a mixed alkaline solution; S13. The mixed salt solution and the mixed alkali solution were added dropwise to the container at the same speed, stirred and reacted, and the pH of the mixed solution was always kept at 11. After the addition was completed, the reaction was heated at 90 ° C for 4h to obtain magnesium aluminum hydrotalcite; S14. The magnesium aluminum hydrotalcite was added to formamide, stirred for 20 hours, and the supernatant was collected by centrifugation, washed and dried to obtain the exfoliated magnesium aluminum hydrotalcite; S15. The stripped magnesium aluminum hydrotalcite was added to a 0.6 mol / L fructose aqueous solution, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution was 8 wt%, and then added to a hydrothermal reactor for heating reaction, the hydrothermal reaction temperature was 185 ° C, the hydrothermal reaction time was 8 h, and a nano-carbon ball / hydrotalcite sheet material was obtained; S16. Add the nano carbon ball / hydrotalcite flake material to anhydrous ethanol, stir and disperse evenly, then add stearic acid, the mass ratio of the nano carbon ball / hydrotalcite flake material and stearic acid is 8:1, mix evenly to obtain a suspension, maintain the solution pH at 5.5, stir to react, and dry to obtain the modified nano carbon ball / hydrotalcite flake material. Example 3 A method for preparing a waterproof, breathable and moisture-permeable fabric, the method comprising the following steps: S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 8.5%, and the TPU was electrospun to obtain a TPU electrospinning membrane with a porosity of 67%; S2. The fabric is immersed in a 0.15wt% chitosan solution, stirred for reaction and then dried, the TPU electrospun membrane is bonded to one side of the fabric layer by hot pressing, and then a layer of chitosan wet gel with a thickness of 0.1mm is coated on the side where the TPU electrospun membrane is not bonded to obtain a fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%; S3. Add the nano carbon ball / hydrotalcite flake material to a chitosan solution with a concentration of 0.9wt%, wherein the concentration of the nano carbon ball / hydrotalcite flake material in the chitosan solution is 7wt%, and stir to mix evenly, and use the side of the fabric layer containing the wet chitosan gel as the receiving surface, and prepare a moisture-repellent waterproof layer with a porosity of 85.5% on the outside of the fabric layer by electrospinning, and finally freeze-dry at a freeze-drying temperature of -45°C for 12h to obtain a waterproof, breathable and moisture-permeable fabric; The method for preparing the nano carbon ball / hydrotalcite flake material comprises the following steps: S11. Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were added to deionized water in a molar ratio of 3:1, and stirred to dissolve to obtain a mixed salt solution; S12. Sodium hydroxide and sodium carbonate were added to deionized water in a molar ratio of 1:1, stirred and dissolved to obtain a mixed alkaline solution; S13. The mixed salt solution and the mixed alkali solution were added dropwise to the container at the same rate, stirred and reacted, and the pH of the mixed solution was always kept at 10. After the addition was completed, the reaction was heated at a temperature of 75 ° C for 8h to obtain magnesium aluminum hydrotalcite; S14. The magnesium aluminum hydrotalcite was added to formamide, stirred for 50 hours, and the supernatant was collected by centrifugation, washed and dried to obtain the exfoliated magnesium aluminum hydrotalcite; S15. The stripped magnesium aluminum hydrotalcite was added to a 0.5 mol / L fructose aqueous solution, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution was 4 wt%, and then added to a hydrothermal reactor for heating reaction, the hydrothermal reaction temperature was 175 ° C, the hydrothermal reaction time was 16 h, and a nano-carbon ball / hydrotalcite sheet material was obtained; S16. Add the nano carbon ball / hydrotalcite flake material to anhydrous ethanol, stir and disperse evenly, then add stearic acid, the mass ratio of the nano carbon ball / hydrotalcite flake material and stearic acid is 6:1, mix evenly to obtain a suspension, maintain the solution pH at 5.5, stir to react, and dry to obtain the modified nano carbon ball / hydrotalcite flake material. Example 4 A method for preparing a waterproof, breathable and moisture-permeable fabric, the method comprising the following steps: S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 9.5%, and the TPU was electrospun to obtain a TPU electrospinning membrane with a porosity of 62%; S2. The fabric is immersed in a 0.25wt% chitosan solution, stirred for reaction and then dried, the TPU electrospun membrane is bonded to one side of the fabric layer by hot pressing, and then a layer of chitosan wet gel with a thickness of 0.2mm is coated on the side where the TPU electrospun membrane is not bonded to obtain a fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%; S3. Add the nano carbon ball / hydrotalcite flake material to a chitosan solution with a concentration of 1.1wt%, wherein the concentration of the nano carbon ball / hydrotalcite flake material in the chitosan solution is 6wt%, and stir to mix evenly, and use the side of the fabric layer containing the wet chitosan gel as the receiving surface, and prepare a moisture-repellent waterproof layer with a porosity of 86.1% on the outside of the fabric layer by electrospinning, and finally freeze-dry at a freeze-drying temperature of -55°C for 18h to obtain a waterproof, breathable and moisture-permeable fabric; The method for preparing the nano carbon ball / hydrotalcite flake material comprises the following steps: S11. Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were added to deionized water in a molar ratio of 3:1, and stirred to dissolve to obtain a mixed salt solution; S12. Sodium hydroxide and sodium carbonate were added to deionized water in a molar ratio of 1:1, stirred and dissolved to obtain a mixed alkaline solution; S13. The mixed salt solution and the mixed alkali solution were added dropwise to the container at the same rate, stirred and reacted, and the pH of the mixed solution was always kept at 11. After the addition was completed, the reaction was heated at a temperature of 85 ° C for 6h to obtain magnesium aluminum hydrotalcite; S14. The magnesium aluminum hydrotalcite was added to formamide, stirred for 30 hours, and the supernatant was collected by centrifugation, washed and dried to obtain the exfoliated magnesium aluminum hydrotalcite; S15. The stripped magnesium aluminum hydrotalcite was added to a 0.3 mol / L fructose aqueous solution, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution was 6 wt%, and then added to a hydrothermal reactor for heating reaction, the hydrothermal reaction temperature was 180 ° C, the hydrothermal reaction time was 12h, and a nano-carbon ball / hydrotalcite sheet material was obtained; S16. Add the nano carbon ball / hydrotalcite flake material to anhydrous ethanol, stir and disperse evenly, then add stearic acid, the mass ratio of the nano carbon ball / hydrotalcite flake material and stearic acid is 7:1, mix evenly to obtain a suspension, maintain the solution pH at 5.5, stir to react, and dry to obtain the modified nano carbon ball / hydrotalcite flake material. Example 5 A method for preparing a waterproof, breathable and moisture-permeable fabric, the method comprising the following steps: S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 9%, and the TPU was electrospun to obtain a TPU electrospinning membrane with a porosity of 66.2%; S2. The fabric is immersed in a 0.2wt% chitosan solution, stirred for reaction and then dried, the TPU electrospun membrane is bonded to one side of the fabric layer by hot pressing, and then a layer of chitosan wet gel with a thickness of 0.13mm is coated on the side where the TPU electrospun membrane is not bonded to obtain a fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%; S3. Adding the nano carbon ball / hydrotalcite flake material to a chitosan solution with a concentration of 1wt%, wherein the concentration of the nano carbon ball / hydrotalcite flake material in the chitosan solution is 6.5wt%, stirring and mixing evenly, using the side of the fabric layer containing the wet chitosan gel as the receiving surface, preparing a moisture-wicking and waterproof layer with a porosity of 88.2% on the outside of the fabric layer by electrospinning, and finally freeze-drying at a freeze-drying temperature of -50°C for 15h to obtain a waterproof, breathable and moisture-permeable fabric; The method for preparing the nano carbon ball / hydrotalcite flake material comprises the following steps: S11. Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were added to deionized water in a molar ratio of 3:1, and stirred to dissolve to obtain a mixed salt solution; S12. Sodium hydroxide and sodium carbonate were added to deionized water in a molar ratio of 1:1, stirred and dissolved to obtain a mixed alkaline solution; S13. The mixed salt solution and the mixed alkali solution were added dropwise to the container at the same speed, stirred and reacted, and the pH of the mixed solution was always kept at 11. After the addition was completed, the reaction was heated at 80 ° C for 7h to obtain magnesium aluminum hydrotalcite; S14. The magnesium aluminum hydrotalcite was added to formamide, stirred for 40 hours, and the supernatant was collected by centrifugation, washed and dried to obtain the exfoliated magnesium aluminum hydrotalcite; S15. The stripped magnesium aluminum hydrotalcite was added to a 0.45 mol / L fructose aqueous solution, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution was 5 wt%, and then added to a hydrothermal autoclave for heating reaction, the hydrothermal reaction temperature was 180 ° C, the hydrothermal reaction time was 15h, and a nano-carbon ball / hydrotalcite sheet material was obtained; S16. Add the nano carbon ball / hydrotalcite flake material to anhydrous ethanol, stir and disperse evenly, then add stearic acid, the mass ratio of the nano carbon ball / hydrotalcite flake material and stearic acid is 6.5:1, mix evenly to obtain a suspension, maintain the solution pH at 5.5, stir to react, and dry to obtain the modified nano carbon ball / hydrotalcite flake material. Comparative Example 1 A method for preparing a waterproof, breathable and moisture-permeable fabric, the method comprising the following steps: S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 9%, and the TPU was electrospun to obtain a TPU electrospinning membrane with a porosity of 63.5%; S2. The fabric is immersed in a 0.2wt% chitosan solution, stirred for reaction and then dried, the TPU electrospun membrane is bonded to one side of the fabric layer by hot pressing, and then a layer of chitosan wet gel with a thickness of 0.13mm is coated on the side where the TPU electrospun membrane is not bonded to obtain a fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%; S3. The modified hydrotalcite flake material is added to a chitosan solution having a concentration of 1 wt%, wherein the concentration of the modified hydrotalcite flake material in the chitosan solution is 6.5 wt%, and after being stirred and mixed evenly, the side of the fabric layer containing the wet chitosan gel is used as the receiving surface, and a moisture-wicking waterproof layer having a porosity of 86.3% is prepared on the outside of the fabric layer by electrospinning, and finally freeze-dried at a freeze-drying temperature of -50°C for 15 hours to obtain a waterproof, breathable and moisture-permeable fabric; The method for preparing the modified hydrotalcite flake material comprises the following steps: S11. Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were added to deionized water in a molar ratio of 3:1, and stirred to dissolve to obtain a mixed salt solution; S12. Sodium hydroxide and sodium carbonate were added to deionized water in a molar ratio of 1:1, stirred and dissolved to obtain a mixed alkaline solution; S13. The mixed salt solution and the mixed alkali solution were added dropwise to the container at the same speed, stirred and reacted, and the pH of the mixed solution was always kept at 11. After the addition was completed, the reaction was heated at 80 ° C for 7h to obtain magnesium aluminum hydrotalcite; S14. The magnesium aluminum hydrotalcite was added to formamide, stirred for 40 hours, and the supernatant was collected by centrifugation, washed and dried to obtain the exfoliated magnesium aluminum hydrotalcite; S15. The exfoliated magnesium aluminum hydrotalcite is added to anhydrous ethanol, stirred and dispersed evenly, and then stearic acid is added. The mass ratio of the exfoliated magnesium aluminum hydrotalcite and stearic acid is 6.5:1. Mix evenly to obtain a suspension. The pH of the solution is maintained at 5.5. The reaction is stirred and dried to obtain a modified hydrotalcite flaky material. Comparative Example 2 A method for preparing a waterproof, breathable and moisture-permeable fabric, the method comprising the following steps: S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 9%, and the TPU was electrospun to obtain a TPU electrospinning membrane with a porosity of 65.5%; S2. The fabric is immersed in a 0.2wt% chitosan solution, stirred for reaction and then dried, the TPU electrospun membrane is bonded to one side of the fabric layer by hot pressing, and then a layer of chitosan wet gel with a thickness of 0.13mm is coated on the side where the TPU electrospun membrane is not bonded to obtain a fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%; S3. Adding the nano carbon ball / hydrotalcite flake material to a chitosan solution with a concentration of 1wt%, wherein the concentration of the nano carbon ball / hydrotalcite flake material in the chitosan solution is 6.5wt%, stirring and mixing evenly, using the side of the fabric layer containing the wet chitosan gel as the receiving surface, preparing a moisture-wicking and waterproof layer with a porosity of 86.5% on the outside of the fabric layer by electrospinning, and finally freeze-drying at a freeze-drying temperature of -50°C for 15h to obtain a waterproof, breathable and moisture-permeable fabric; The method for preparing the nano carbon ball / hydrotalcite flake material comprises the following steps: S11. Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were added to deionized water in a molar ratio of 3:1, and stirred to dissolve to obtain a mixed salt solution; S12. Sodium hydroxide and sodium carbonate were added to deionized water in a molar ratio of 1:1, stirred and dissolved to obtain a mixed alkaline solution; S13. The mixed salt solution and the mixed alkali solution were added dropwise to the container at the same speed, stirred and reacted, and the pH of the mixed solution was always kept at 11. After the addition was completed, the reaction was heated at 80 ° C for 7h to obtain magnesium aluminum hydrotalcite; S14. The magnesium aluminum hydrotalcite was added to formamide, stirred for 40 hours, and the supernatant was collected by centrifugation, washed and dried to obtain the exfoliated magnesium aluminum hydrotalcite; S15. The stripped magnesium aluminum hydrotalcite is added to a 0.45 mol / L fructose aqueous solution, where the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution is 5 wt %, and then added to a hydrothermal kettle for heating reaction at a temperature of 180°C for 15 h to obtain a nano-carbon ball / hydrotalcite sheet material. Comparative Example 3 A method for preparing a waterproof, breathable and moisture-permeable fabric, the method comprising the following steps: S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 9%, and the TPU was electrospun to obtain a TPU electrospinning membrane with a porosity of 64.5%; S2. The TPU electrospun membrane is bonded to one side of the fabric layer by hot pressing, and then a layer of chitosan wet gel with a thickness of 0.13 mm is coated on the side of the TPU electrospun membrane that is not bonded to obtain a fabric layer, wherein the mass fraction of the chitosan wet gel is 2 wt %; S3. Adding the nano carbon ball / hydrotalcite flake material to a chitosan solution with a concentration of 1wt%, wherein the concentration of the nano carbon ball / hydrotalcite flake material in the chitosan solution is 6.5wt%, stirring and mixing evenly, using the side of the fabric layer containing the wet chitosan gel as the receiving surface, preparing a moisture-wicking and waterproof layer with a porosity of 85.9% on the outside of the fabric layer by electrospinning, and finally freeze-drying at a freeze-drying temperature of -50°C for 15h to obtain a waterproof, breathable and moisture-permeable fabric; The method for preparing the nano carbon ball / hydrotalcite flake material comprises the following steps: S11. Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were added to deionized water in a molar ratio of 3:1, and stirred to dissolve to obtain a mixed salt solution; S12. Sodium hydroxide and sodium carbonate were added to deionized water in a molar ratio of 1:1, stirred and dissolved to obtain a mixed alkaline solution; S13. The mixed salt solution and the mixed alkali solution were added dropwise to the container at the same speed, stirred and reacted, and the pH of the mixed solution was always kept at 11. After the addition was completed, the reaction was heated at 80 ° C for 7h to obtain magnesium aluminum hydrotalcite; S14. The magnesium aluminum hydrotalcite was added to formamide, stirred for 40 hours, and the supernatant was collected by centrifugation, washed and dried to obtain the exfoliated magnesium aluminum hydrotalcite; S15. The stripped magnesium aluminum hydrotalcite was added to a 0.45 mol / L fructose aqueous solution, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution was 5 wt%, and then added to a hydrothermal autoclave for heating reaction, the hydrothermal reaction temperature was 180 ° C, the hydrothermal reaction time was 15h, and a nano-carbon ball / hydrotalcite sheet material was obtained; S16. Add the nano carbon ball / hydrotalcite flake material to anhydrous ethanol, stir and disperse evenly, then add stearic acid, the mass ratio of the nano carbon ball / hydrotalcite flake material and stearic acid is 6.5:1, mix evenly to obtain a suspension, maintain the solution pH at 5.5, stir to react, and dry to obtain the modified nano carbon ball / hydrotalcite flake material. Comparative Example 4 A method for preparing a waterproof, breathable and moisture-permeable fabric, the method comprising the following steps: S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 9%, and the TPU was electrospun to obtain a TPU electrospinning membrane with a porosity of 61.5%; S2. The fabric was immersed in a 0.2wt% chitosan solution, stirred for reaction and dried, and the TPU electrospun membrane was bonded to one side of the fabric layer by hot pressing to obtain a fabric layer; S3. Adding the nano carbon ball / hydrotalcite flake material to a chitosan solution with a concentration of 1wt%, wherein the concentration of the nano carbon ball / hydrotalcite flake material in the chitosan solution is 6.5wt%, stirring and mixing evenly, using the unbonded side of the fabric layer as the receiving surface, preparing a moisture-wicking and waterproof layer with a porosity of 86.2% on the outer side of the fabric layer by electrospinning, and finally freeze-drying at a freeze-drying temperature of -50°C for 15h to obtain a waterproof, breathable and moisture-permeable fabric; The method for preparing the nano carbon ball / hydrotalcite flake material comprises the following steps: S11. Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were added to deionized water in a molar ratio of 3:1, and stirred to dissolve to obtain a mixed salt solution; S12. Sodium hydroxide and sodium carbonate were added to deionized water in a molar ratio of 1:1, stirred and dissolved to obtain a mixed alkaline solution; S13. The mixed salt solution and the mixed alkali solution were added dropwise to the container at the same speed, stirred and reacted, and the pH of the mixed solution was always kept at 11. After the addition was completed, the reaction was heated at 80 ° C for 7h to obtain magnesium aluminum hydrotalcite; S14. The magnesium aluminum hydrotalcite was added to formamide, stirred for 40 hours, and the supernatant was collected by centrifugation, washed and dried to obtain the exfoliated magnesium aluminum hydrotalcite; S15. The stripped magnesium aluminum hydrotalcite was added to a 0.45 mol / L fructose aqueous solution, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution was 5 wt%, and then added to a hydrothermal autoclave for heating reaction, the hydrothermal reaction temperature was 180 ° C, the hydrothermal reaction time was 15h, and a nano-carbon ball / hydrotalcite sheet material was obtained; S16. Add the nano carbon ball / hydrotalcite flake material to anhydrous ethanol, stir and disperse evenly, then add stearic acid, the mass ratio of the nano carbon ball / hydrotalcite flake material and stearic acid is 6.5:1, mix evenly to obtain a suspension, maintain the solution pH at 5.5, stir to react, and dry to obtain the modified nano carbon ball / hydrotalcite flake material. Comparative Example 5 A method for preparing a waterproof, breathable and moisture-permeable fabric, the method comprising the following steps: S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 9%, and the TPU was electrospun to obtain a TPU electrospinning membrane with a porosity of 67.5%; S2. The fabric is immersed in a 1wt% chitosan solution, stirred for reaction and then dried, the TPU electrospun membrane is bonded to one side of the fabric layer by hot pressing, and then a layer of chitosan wet gel with a thickness of 0.13 mm is coated on the side where the TPU electrospun membrane is not bonded to obtain a fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%; S3. Add the nano carbon ball / hydrotalcite flake material to a chitosan solution with a concentration of 1wt%, wherein the concentration of the nano carbon ball / hydrotalcite flake material in the chitosan solution is 6.5wt%, and stir to mix evenly. Then, use the side of the fabric layer containing the wet chitosan gel as the receiving surface, and prepare a moisture-repellent waterproof layer with a porosity of 86.1% on the outside of the fabric layer by electrospinning. Finally, freeze-dry at a freeze-drying temperature of -50°C for 15 hours to obtain a waterproof, breathable, and moisture-permeable fabric. The method for preparing the nano carbon ball / hydrotalcite flake material comprises the following steps: S11. Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were added to deionized water in a molar ratio of 3:1, and stirred to dissolve to obtain a mixed salt solution; S12. Sodium hydroxide and sodium carbonate were added to deionized water in a molar ratio of 1:1, stirred and dissolved to obtain a mixed alkaline solution; S13. The mixed salt solution and the mixed alkali solution were added dropwise to the container at the same speed, stirred and reacted, and the pH of the mixed solution was always kept at 11. After the addition was completed, the reaction was heated at 80 ° C for 7h to obtain magnesium aluminum hydrotalcite; S14. The magnesium aluminum hydrotalcite was added to formamide, stirred for 40 hours, and the supernatant was collected by centrifugation, washed and dried to obtain the exfoliated magnesium aluminum hydrotalcite; S15. The stripped magnesium aluminum hydrotalcite was added to a 0.45 mol / L fructose aqueous solution, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution was 5 wt%, and then added to a hydrothermal autoclave for heating reaction, the hydrothermal reaction temperature was 180 ° C, the hydrothermal reaction time was 15h, and a nano-carbon ball / hydrotalcite sheet material was obtained; S16. Add the nano carbon ball / hydrotalcite flake material to anhydrous ethanol, stir and disperse evenly, then add stearic acid, the mass ratio of the nano carbon ball / hydrotalcite flake material and stearic acid is 6.5:1, mix evenly to obtain a suspension, maintain the solution pH at 5.5, stir to react, and dry to obtain the modified nano carbon ball / hydrotalcite flake material. Performance tests of the fabrics prepared in Examples 1-5 and Comparative Examples 1-5: In the above embodiments and comparative examples, the fabric layer is made of 230T polyester taffeta, the hydrostatic pressure is tested by GB / T 4744-2013 "Hydrostatic pressure method for testing and evaluating the waterproof performance of textiles", and the moisture permeability is mainly tested by the evaporation method, i.e. GB / T 12704.2-2009 "Test method for moisture permeability of textile fabrics Part 2: Evaporation method". Table 1 shows the waterproof and moisture permeability values of the fabric before washing According to GB / T 32614-2016 "Outdoor Sportswear Jackets", the functional requirements for jacket fabrics at level I are as follows: the moisture permeability before washing should be ≥ 5000g / (m 2 ·24h), hydrostatic pressure ≥50kPa, the above embodiments and comparative examples can achieve the Class I function of the jacket fabric. Table 2 shows the waterproof and moisture permeability values of the fabric after washing Hydrostatic pressure / kPa <![CDATA[Water vapor transmission rate g / (m 2 ·24h)]]> Example 1 126 12154 Example 2 122 12899 Example 3 120 12569 Example 4 120 12871 Example 5 123 13001 Comparative Example 1 78 12956 Comparative Example 2 45 12873 Comparative Example 3 119 11063 Comparative Example 4 125 8865 Comparative Example 5 122 7812 Wash three times according to the 5A washing procedure in GB / T 8629-2001 "Household Washing and Drying Procedure for Textile Testing". The waterproof performance is slightly affected after washing, but the moisture permeability is good. Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A waterproof, breathable and moisture-permeable fabric, characterized in that: The fabric comprises a TPU layer, a fabric layer, and a moisture-removing and waterproof layer. The TPU layer is a TPU electrostatic spinning membrane, and the moisture-removing and waterproof layer is a chitosan electrostatic spinning membrane, and the chitosan electrostatic spinning membrane contains nano carbon ball / hydrotalcite flake material.
2. The waterproof, breathable and moisture-permeable fabric according to claim 1, characterized in that: The method for preparing the nano carbon ball / hydrotalcite flake material comprises the following steps: S11. Magnesium nitrate hexahydrate and aluminum nitrate nonahydrate were added to deionized water in a molar ratio of 3:1, and stirred to dissolve to obtain a mixed salt solution; S12. Sodium hydroxide and sodium carbonate were added to deionized water in a molar ratio of 1:1, stirred and dissolved to obtain a mixed alkaline solution; S13. The mixed salt solution and the mixed alkali solution were added dropwise to the container at the same rate, stirring the reaction, always maintaining the pH of the mixed solution at 10-11, and the reaction was heated after the addition was completed to obtain magnesium aluminum hydrotalcite; S14. The magnesium aluminum hydrotalcite was added to formamide, stirred for 20-60h, and the supernatant was collected by centrifugation, washed and dried to obtain the exfoliated magnesium aluminum hydrotalcite; S15. The exfoliated magnesium aluminum hydrotalcite is added to a fructose aqueous solution, and then added to a hydrothermal reactor for heating to react to obtain a nano-carbon ball / hydrotalcite sheet material; S16. Add the nano carbon sphere / hydrotalcite flake material to anhydrous ethanol, stir and disperse evenly, then add stearic acid, mix evenly to obtain a suspension, maintain the solution pH at 5.5, stir to react, and dry to obtain a modified nano carbon sphere / hydrotalcite flake material.
3. The waterproof, breathable and moisture-permeable fabric according to claim 2, characterized in that: The heating reaction temperature in step S13 is 70-90° C. and the time is 4-10 hours.
4. The waterproof, breathable and moisture-permeable fabric according to claim 2, characterized in that: In step S15, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution is 2-8wt%, the concentration of the fructose aqueous solution is 0.2-0.6mol / L, the hydrothermal reaction temperature is 170-185°C, and the hydrothermal reaction time is 8-20h.
5. The waterproof, breathable and moisture-permeable fabric according to claim 2, characterized in that: In the step S16, the mass ratio of the nano carbon balls / hydrotalcite flake material to stearic acid is 5-8:
1.
6. The method for preparing the waterproof, breathable and moisture-permeable fabric according to claim 1, characterized in that: The preparation method comprises the following steps: S1. dissolving thermoplastic polyurethane in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 8-10%, and electrospinning the TPU to obtain a TPU electrospinning membrane; S2. The fabric is immersed in a 0.1-0.3wt% chitosan solution, stirred for reaction and then dried, the TPU electrospun membrane is bonded to one side of the fabric layer by hot pressing, and then a layer of chitosan wet gel is coated on the side of the TPU electrospun membrane that is not bonded to obtain a fabric layer; S3. Add the nano carbon ball / hydrotalcite flake material to the chitosan solution, stir and mix evenly, use the side of the fabric layer containing the chitosan wet gel as the receiving surface, and prepare a moisture-repelling and waterproof layer on the outside of the fabric layer through electrospinning, and finally freeze-dry to obtain a waterproof, breathable and moisture-permeable fabric.
7. The method for preparing the waterproof, breathable and moisture-permeable fabric according to claim 6, characterized in that: The porosity of the electrospinning membrane in step S1 is 60-70%.
8. The method for preparing the waterproof, breathable and moisture-permeable fabric according to claim 6, characterized in that: The thickness of the chitosan hydrogel in step S2 is 0.1-0.2 mm.
9. The method for preparing the waterproof, breathable and moisture-permeable fabric according to claim 6, characterized in that: In step S3, the concentration of the nano carbon ball / hydrotalcite flake material in the chitosan solution is 5-8wt%, the concentration of the chitosan solution is 0.8-1.2wt%, and the porosity of the moisture-repellent and waterproof layer is 80-90%.
10. The method for preparing the waterproof, breathable and moisture-permeable fabric according to claim 6, characterized in that: In step S3, the freeze drying temperature is -60 to -40°C and the time is 10 to 20 hours.
Citation Information
Patent Citations
Multi-element composite metal oxide hollow nanosphere and preparation method thereof
CN102671645A
chitosan composite fabric production method
CN103879107A
Preparation method of hierarchical composite electrostatic spinning waterproof moisture-permeable film with antibacterial property
CN111020883A
Preparation method of waterproof moisture-permeable antibacterial nanofiber membrane
CN114657707A
Waterproof electrostatic spinning membrane with high moisture permeability and air permeability as well as preparation method and application thereof
CN117468172A
Cited By
Waterproof electrostatic spinning fiber fabric
CN122165720A
Waterproof electrospun fibrous fabric
CN122165720B